Implementation of the Floyd-Warshall Algorithm and Bellman-Ford Algorithm to Determine the Shortest Path in the Distribution of LPG Gas - Yusuf Moh. Rizky; Nurwan Nurwan; Wungguli Djihad; Yahya Lailany (E3S Web of Conferences, 2023)
In this article, the method use to determine the shortest path in the distribution of LPG is the Floyd-Warshall algorithm and the Bellman-Ford algorithm. These two methods will be compared to find out methods that can provide the best result. The best result is the path that has the minimum distance of distribution of LPG. Both of these algorithms are focused on simulating calculations that begin by representing the map in the form of a graph. Finally, the results obtained from this study are that using the Floyd-Warshall algorithm produces a path with a total distance of 111.05 KM while the Bellman-Ford algorithm produces 332.3 KM.